A Case of Lymphangioma Circumscriptum with Four Times Recurrence - Coşkun, Başak Kandi; Saral, Yunus; Ataseven, Arzu (Fırat University, 2004)
Lymphangioma circumscriptum is a lymphatic malformation which is localized to an area of skin, subcutaneous tissue and sometimes muscle.The etiology of disease is unkown, but obstruction of the lymph vessels has been suggested as a possible cause in some cases. The most comman locations are the oral mucosa, proximal aspects of the limbs, groin, axilla and trunk. We report a 12 years old male patient abdomen location with lymphangioma circumscriptum case according to literature. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Lenfanjioma sircumscriptum (LS) deri, subkutan doku ve nadiren de kas tabakasında yerleşen lenfatik bir malformasyondur. Hastalığın etiyolojisi bilinmemekte ancak bazı olgularda olası nedenin lenf damarlarının obstruksiyonu olabileceği düşünülmektedir. En sık yerleşim yeri oral mukoza, ekstremitelerin proksimalleri, kasık, aksilla, ve gövdedir. Burada 12 yaşında erkek çocukta saptanan abdomen yerleşimli LS olgusu sunulmuş ve literatür ışığında tartışılmıştır. ©2004, Fırat Üniversitesi, Tıp Fakültesi
Dört Kez Nükseden Lenfanjioma Sircumscriptum Olgusu